Targeted exosome‐encapsulated erastin induced ferroptosis in triple negative breast cancer cells - Yu, Mengyu; Gai, Chengcheng; Li, Zihaoran; Ding, Dejun; Zheng, Jie; Zhang, Weifen; Lv, Shijun; Li, Wentong (Cancer science, 2019)
Ferroptosis is an iron‐dependent, lipid peroxide‐driven cell death caused by inhibition of the cystine/glutamate transporter, which is of importance for the survival of triple‐negative breast cancer (TNBC) cells. Erastin is a low molecular weight chemotherapy drug that induces ferroptosis; however, poor water solubility and renal toxicity have limited its application. Exosomes, as drug delivery vehicles with low immunogenicity, high biocompatibility and high efficiency, have attracted increasing attention in recent years. Herein, we developed a formulation of erastin‐loaded exosomes labeled with folate (FA) to form FA‐vectorized exosomes loaded with erastin (erastin@FA‐exo) to target TNBC cells with overexpression of FA receptors. The characterization, drug release, internalization and anti–tumor effect in vitro of erastin@FA‐exo were determined. Erastin@FA‐exo could increase the uptake efficiency of erastin into MDA‐MB‐231 cells; compared with erastin@exo and free erastin, erastin@FA‐exo has a better inhibitory effect on the proliferation and migration of MDA‐MB‐231 cells. Furthermore, erastin@FA‐exo promoted ferroptosis with intracellular depletion of glutathione and reactive oxygen species overgeneration. Western blot analyses revealed that erastin@FA‐exo suppressed expression of glutathione peroxidase 4 (GPX4) and upregulated expression of cysteine dioxygenase (CDO1). We conclude that targeting and biocompatibility of exosome‐based erastin preparations provide an innovative and powerful delivery platform for anti–cancer therapy. Exosome was isolated from serum‐free cell culture medium by differential centrifugation, and then erastin was loaded into exosomes with ultrasonic, and then FA was modified on erastin@exo. Then erastin@FA‐exo was characterized by TEM and DLS, and erastin@FA‐exo was evaluated by HPLC. In the cell experiment, in order to compare the killing effect of erastin@FA‐exo, erastin@exo and free erastin on MDA‐MB‐231 cells, we conducted cell viability assay, EdU assay and flow cytometric analysis, etc., and then we tested the ROS and GSH experiments to detect the reactive oxygen species generated by the cells after drug addition, and at the same time we detected the mitochondrial membrane potential of the cells. These results all proved that erastin@ FA‐exo was more effective in killing MDA‐MB‐231 cells.